2023
DOI: 10.3390/polym15061490
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Organic Frameworks Applications in Synergistic Cancer Photo-Immunotherapy

Abstract: Conventional cancer therapies, such as radiotherapy and chemotherapy, can have long-term side effects. Phototherapy has significant potential as a non-invasive alternative treatment with excellent selectivity. Nevertheless, its applicability is restricted by the availability of effective photosensitizers and photothermal agents, and its low efficacy when it comes to avoiding metastasis and tumor recurrence. Immunotherapy can promote systemic antitumoral immune responses, acting against metastasis and recurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 201 publications
(310 reference statements)
0
3
0
Order By: Relevance
“…The platforms that are currently performing the best in terms of biocompatibility and bioavailability are those that are less than 200 nm in size, have a hydrophilic surface, and have a somewhat stable framework under physiological pH. Fernandes et al 2023 [36] observed in what way the difficult anticancer medicine prednisolone's functional groups affect interactions with nano-MOFs and release in various mediums. It was discovered that proteins that are bigger than the nanoMOFs' windows were adsorbed at their exterior surfaces, however, the porosity allowed the charged particles from the suspended media to diffuse off the nanoMOFs.…”
Section: Metal-organic Framework-based Nanomaterials For Biomedical A...mentioning
confidence: 99%
“…The platforms that are currently performing the best in terms of biocompatibility and bioavailability are those that are less than 200 nm in size, have a hydrophilic surface, and have a somewhat stable framework under physiological pH. Fernandes et al 2023 [36] observed in what way the difficult anticancer medicine prednisolone's functional groups affect interactions with nano-MOFs and release in various mediums. It was discovered that proteins that are bigger than the nanoMOFs' windows were adsorbed at their exterior surfaces, however, the porosity allowed the charged particles from the suspended media to diffuse off the nanoMOFs.…”
Section: Metal-organic Framework-based Nanomaterials For Biomedical A...mentioning
confidence: 99%
“…This approach can potentially overcome the aggregation-caused quenching (ACQ) effect often seen in PDT, as well as increase the efficacy of the treatment by facilitating ROS diffusion ( 58 , 59 ). Nanosized metal-organic Frameworks (nMOFs) incorporate PSs as structural units, producing adjustable and permeable structures that surmount the ACQ effect and permit significant PS loads ( 60 , 61 ). These permeable structures not only efficiently disperse PSs but also promote ROS diffusion, thus improving the efficacy of PDT ( 58 , 62 ).…”
Section: Advanced Pss For Pdtmentioning
confidence: 99%
“…33,34 PTT can be divided into two approaches based on the temperature range reached during treatment. 35,36 Mild photothermal therapy (40−50 °C) disrupts normal cellular functioning by increasing the cell membrane permeability and cellular uptake, disrupting metabolic signaling. This allows for selective treatment, as cancer cell membranes are typically more sensitive to heat, increasing permeability and internalization of nanomaterials/ drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Photothermal therapy (PTT), one of the most commonly used phototherapy modalities, is a therapeutic approach based on visible or near-infrared (NIR)-absorbing agents that allow the conversion of light energy into heat, ultimately leading to the destruction of cancer cells . PTT has increased specificity because PTT agents preferentially accumulate at the site of the lesion and irradiation is focused on the tumor area. , PTT can be divided into two approaches based on the temperature range reached during treatment. , Mild photothermal therapy (40–50 °C) disrupts normal cellular functioning by increasing the cell membrane permeability and cellular uptake, disrupting metabolic signaling. This allows for selective treatment, as cancer cell membranes are typically more sensitive to heat, increasing permeability and internalization of nanomaterials/drugs. , Photothermal ablation uses temperatures above 50 °C, resulting in cell membrane destruction and tissue necrosis. ,, …”
Section: Introductionmentioning
confidence: 99%